The role of personal motivation in sustainable purchasing practices - Gyöngyi Vörösmarty; Imre Dobos (Amfiteatru Economic Journal, 2019)
There is growing interest in identifying the drivers of and barriers to green purchasing, and many publications focus on motivational factors. However, the effects of these factors on the activities and means applied to sustainable purchasing are seldom investigated. This paper addresses this research gap and examines the impact of the motivational factors on green purchasing practices of the companies'. This paper also emphasises the role and motivational background of personal attitudes and reveals that there are differences among them. Based on the literature, a questionnaire was developed and a survey was completed in Hungary. The answers indicate that positive and compliant personal attitudes of purchasing managers' have different drivers and barriers, while differences are also present in sustainable purchasing practices. Purchasing managers with a positive personal attitude have better green purchasing practices but mainly concerning product performance level activities, which do not require in-depth green management information.
Keywords: C10; M11; Q01; 330; sustainable purchasing; motivation; purchasing practices; sustainable supply chain management